Community Facilitator: Human Resources Or Human Capital? (International Journal of Scientific Research and Management (IJSRM), 2022)
Community Facilitator is indispensable in the development programs that use a community-based approach. Its existence has been an integral part of community-driven development since the early 1980s. The question is, is it human resources or human capital? What competencies must a facilitator have to carry out their duties effectively? This research was conducted with a qualitative approach through FGD and interviews with informants to answer the following questions: (i) what is a facilitator? (ii) how does the facilitator work? (iii) what competencies must the facilitator have? (iv) what is the difference between human resources and human capital? (v) is the facilitator a human resource or human capital? In this research, the facilitator’s competence will be identified using the KSA framework (knowledge, skill, and attribute). Based on the study, a facilitator is defined as a person with certain knowledge, skills, and attributes, who is assigned to introduce, plan, and organize the implementation of a program to the program beneficiaries so that the program can be implemented following the predetermined budget, provisions, quality, and procedures. Facilitators must know the program cycle, local culture/tradition, formal and informal figures in the village, and the resources required for the program implementation. The facilitator’s must-have skills include communication, organizing, mediation, administration-finance, and various construction technical skills. Meanwhile, the attributes needed include commitment, responsibility, and adaptation. A human resource is a worker using knowledge, skills, and commitment to carry out tasks with clearly defined processes and outputs. Human capital is a worker who uses knowledge, skills, creativity, innovativeness, and commitment to carry out tasks to increase the organizational value-added, with processes and outputs that have not been clearly defined. From an individual and organizational perspective, community facilitator is categorized as human capital.